2021
DOI: 10.1101/2021.12.16.472949
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prolonged nicotine exposure reduces aversion to the drug in mice by altering nicotinic transmission in the interpeduncular nucleus

Abstract: Nicotine intake is likely to result from a balance between the rewarding and aversive properties of the drug, yet the individual differences in neural activity that control aversion to nicotine and their adaptation during the addiction process remain largely unknown. Using a two-bottle choice experiment, we observed a high heterogeneity in nicotine-drinking profiles in isogenic adult male mice, with about half of the mice persisting in consuming nicotine even at high concentrations, whereas the other half dura… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 57 publications
(125 reference statements)
2
6
0
Order By: Relevance
“…[10][11][12][13] These competing reinforcing and aversive properties of nicotine, together with the feeling of satiety, are consistent with the observation that humans and laboratory rodents titrate their nicotine intake when high doses are available. 5,11,12,14 The aversive effect of high-dose nicotine involves the neural pathway projecting from the medial habenula (Mhb) to the interpeduncular nucleus (IPN). 5,10,11 Neurons belonging to this pathway express high densities of rare nAChR subunits, notably a3, a5 and β4.…”
Section: Introductionsupporting
confidence: 79%
See 3 more Smart Citations
“…[10][11][12][13] These competing reinforcing and aversive properties of nicotine, together with the feeling of satiety, are consistent with the observation that humans and laboratory rodents titrate their nicotine intake when high doses are available. 5,11,12,14 The aversive effect of high-dose nicotine involves the neural pathway projecting from the medial habenula (Mhb) to the interpeduncular nucleus (IPN). 5,10,11 Neurons belonging to this pathway express high densities of rare nAChR subunits, notably a3, a5 and β4.…”
Section: Introductionsupporting
confidence: 79%
“…These results are consistent with previous data obtained using the juxtacellular technique in neurons that were labelled and confirmed to be located in the IPN. 12 We then assessed the sensitivity of IPN neurons to a range of nicotine doses (7.5 to 60 µg/kg) and found that the effect of nicotine was dose-dependent, but that the polarity of the response (i.e., activation or inhibition) was not. Indeed, neurons that were activated by nicotine at 30 µg/kg were activated across all doses tested, and similarly, inhibited neurons maintained their inhibition at all doses (Figure 2D).…”
Section: Dose-dependent Effects Of Nicotine On Ipn Neurons In Vivomentioning
confidence: 99%
See 2 more Smart Citations
“…We propose that this may be one mechanism by which nicotine use in adolescence creates an enduring vulnerability to later nicotine use and addiction. An imbalance between the rewarding and aversive effects of nicotine has indeed been posited as a mechanism driving the transition from casual use to addiction 61,[90][91][92] .…”
Section: Discussionmentioning
confidence: 99%